2015
DOI: 10.1158/1078-0432.ccr-14-2824
|View full text |Cite
|
Sign up to set email alerts
|

Ablative Tumor Radiation Can Change the Tumor Immune Cell Microenvironment to Induce Durable Complete Remissions

Abstract: Purpose The goals of the study were to elucidate the immune mechanisms that contribute to desirable complete remissions of murine colon tumors treated with single radiation dose of 30 Gy. This dose is at the upper end of the ablative range used clinically to treat advanced or metastatic colorectal, liver, and non-small cell lung tumors. Experimental design Changes in the tumor immune microenvironment of single tumor nodules exposed to radiation were studied using 21 day (>1 cm in diameter) CT26 and MC38 colo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
341
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 396 publications
(361 citation statements)
references
References 55 publications
11
341
3
6
Order By: Relevance
“…23 In contrast, 10 daily 3-Gy fractions failed to lead to a robust T-cell infiltration in these tumours, resulting in poorer local control. 23 A single high dose fraction of radiation has also been shown to enhance presentation and T-cell recognition of tumour-associated antigens, 24 but in contrast this phenomenon was not seen in a melanoma model with a RT schedule at 7.5 Gy/fraction.…”
Section: Stereotactic Radiation-a Novel Opportunity To Improve Radiotmentioning
confidence: 90%
See 2 more Smart Citations
“…23 In contrast, 10 daily 3-Gy fractions failed to lead to a robust T-cell infiltration in these tumours, resulting in poorer local control. 23 A single high dose fraction of radiation has also been shown to enhance presentation and T-cell recognition of tumour-associated antigens, 24 but in contrast this phenomenon was not seen in a melanoma model with a RT schedule at 7.5 Gy/fraction.…”
Section: Stereotactic Radiation-a Novel Opportunity To Improve Radiotmentioning
confidence: 90%
“…23 In contrast, 10 daily 3-Gy fractions failed to lead to a robust T-cell infiltration in these tumours, resulting in poorer local control. 23 A single high dose fraction of radiation has also been shown to enhance presentation and T-cell recognition of tumour-associated antigens, 24 but in contrast this phenomenon was not seen in a melanoma model with a RT schedule at 7.5 Gy/fraction. 25 As more evidence emerges, the specific hypofractionated or ablative radiation schedule required to improve the immune response may turn out to be tumour specific and be dependent on radiosensitivity and the nature and kinetics of the RTinduced ICD.…”
Section: Stereotactic Radiation-a Novel Opportunity To Improve Radiotmentioning
confidence: 90%
See 1 more Smart Citation
“…6,7 The goal of our recent study was to determine whether a single high dose of radiation targeted to advanced CT26 and MC38 murine subcutaneous colon tumors can induce durable complete remissions. 8 We also determined whether induction of antitumor immunity was required, and radiation induced immunity was reflected in changes in the tumor microenvironment. 8 We found that increasing the single dose of radiation resulted in an increased incidence of durable remissions, and an incidence of about 90% was achieved with 30 Gy, the maximum dose of stereotactic body radiation therapy (SBRT) used clinically.…”
Section: Foxp3mentioning
confidence: 99%
“…8 We also determined whether induction of antitumor immunity was required, and radiation induced immunity was reflected in changes in the tumor microenvironment. 8 We found that increasing the single dose of radiation resulted in an increased incidence of durable remissions, and an incidence of about 90% was achieved with 30 Gy, the maximum dose of stereotactic body radiation therapy (SBRT) used clinically. Remissions were dependent on T cell immunity, since RAG-2 ¡/¡ mice lacking adaptive immune cells and mice depleted of CD4…”
Section: Foxp3mentioning
confidence: 99%